PENGARUH pH AWAL MEDIA DAN LAMA FERMENTASI TERHADAP PRODUKSI KALSIUM SITRAT DARI LIMBAH BREM DENGAN MENGGUNAKAN Aspergillus niger ATCC 16404 - Adi Wagestu, I Wayan; Semadi Antara, Nyoman; Ganda Putra, G.P. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 4 (2016): Desember, 2017)
Brem waste has sugar content of 12% and its starch content is 10.8%. Components contained in the brem waste are expected to be able to be used to produce Ca-citrate  The purpose of this research was to find out the media’s initial pH effect and fermentation time on Ca-citrate production from brem waste by using Aspergillus niger ATCC 16404. The research was an experimental research using the randomized block design with the factorial experimentpattern that consists of two factors. The first factor was the media’s initial pH (3, 4, 5, and 6), and the second factor was the fermentation time (3, 5, and 7 days). The result showed that theinitial pH of medium fermentation affected the medium pH after fermentation and production of Ca-citrate, but it didn’t influence  the  total  soluble solid  of  medium  fermentation.Fermentation time  influenced  Ca-citrate  production, final pH, and total soluble solid  of fermentation medium. The fermentation with media’s initial pH of 5 and the fermentation for5 days was the best combination treatments  to  produce  Ca-citrate  which the production levelwas 5,35 ± 0,06 g/L. [Keywords]:  Aspergillus niger  ATCC 16404, brem waste  flour, pH, fermentation time,  Cacitrate
Keywords: 123